Bahasa Indonesia language program impact analysis in the Polytechnic University of the Philippines Manila: a basis for the bahasa Indonesia’s inclusion in the ab English language studies’ and ab literary and cultural studies’ curriculum - Rolando P. Quinones, Jr.; Marissa L. Mayrena (Badan Pengembangan dan Pembinaan Bahasa, 2020)
The present study aims to know the impact of the Bahasa Indonesia (BIPA) training on enabling the macro skills among the 144 respondents from the Polytechnic University of the Philippines in Sta. Mesa, Manila as well as the perceived benefits of including the language as one of the foreign language courses in the respondents’ curriculum. The researchers used the descriptive research design. The respondents were selected using purposive sampling and the data were gathered through a survey form with 9 questions. Through the grand mean, it was found out that powerpoint presentations were impactful in enabling them to perform reading tasks. Writing paragraphs were impactful for their writing tasks while Listening to lecture and doing dialogues were impactful for enabling them to perform listening and speaking tasks. Opportunity to work in other South East Asian Countries emerged as the mostly agreed benefit of including Bahasa Indonesia in the curriculum.